Pengukuran Kinerja Manajemen Rantai Pasok di Perusahaan Logistik dengan Model SCOR 11 - Muhammad Ave Sina (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
Business rivalry nowadays involves more than just one advantage of a good or service provided the owner of the good or service must also could enhance the advantages of the good or service itself. so that customers can get several benefits from a single good or service. Customers will begin to avoid similar items and services in favor of those made by businesses that can produce their goods with a multitude of advantages if a firm can accomplish this with quality that doesn't suffer. Companies that sell a variety of goods, one of which is in the logistics industry. The growth of e-commerce has raised this logistics company's value. If supply chain management is used in logistics organizations, it will be particularly relevant because there are numerous parties involved. PT. X is among the logistics firms having adopted supply chain management. As the logistics industry becomes more competitive, PT. X has also incorporated supply chain management. In order to evaluate PT Source's supply chain management performance, five criteria reliability, responsiveness, cost, agility and asset management along with make, delivery and return are taken into consideration. Reported to the testing results of this study, the reliability attribute's value at the process source is 100%, meaning it needs to be preserved. Subsequently, the attribute's value in the delivery process is 36.90%, and the attribute's response takes 9 days. The attribute fee is IDR 1,447,150,000.00 in the interim. Next, the asset management attribute is IDR 1,584,318,187.00, and the agility attribute is 3 days.